3D printing technology; methods, biomedical applications, future opportunities and trends - BOZKURT, YAHYA (ELSEVIER, 2021)
3D printer technology is one of the innovations brought by the industrial age. It has been in our lives for many years. It is rapidly developing and used in many sectors like aviation and defence industry. This miracle manufacturing method has been frequently preferred for medical applications in recent years. In this study, 3D printer technology is introduced, various method of 3D printing are mentioned and the use of this technology in biomedical applications is referred. The use of 3D printing in surgery, pharmaceutical industry, disease modelling, development of customized implants and prostheses, organ printing, vet medicine and tissue engineering applications have been explained and this new method compared with traditional methods that used in the biomedical field. In addition, this study includes future opportunities that are expected to become widespread and developed in the future. (c) 2021 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: 3D printers; Additive manufacturing; Biomedical applications; Biomaterial; Bioprinting; MECHANICAL-PROPERTIES; MEDICAL APPLICATIONS; FACE SHIELDS; TISSUE; DESIGN; SCAFFOLDS; MODELS; IMPLANTS; CELL; STEREOLITHOGRAPHY